Review of Leonidas Moiras, Η ελληνική Επανάσταση μέσα από τα μάτια των Οθωμανών : [The Greek Revolution through Ottoman eyes] - Spyropoulos, Yannis (Historein, 2022)
Review of Leonidas Moiras, Η ελληνική Επανάσταση μέσα από τα μάτια των Οθωμανών [The Greek Revolution through Ottoman eyes]. Athens: Topos, 2020. 232 pp. To view the full text, click on the button "HTML".